The Meaning of Work Among Nonstandard Workers: A Multifaceted Reality - Bujold, Charles; Fournier, Geneviève; Lachance, Lise (Canadian Journal of Counselling and Psychotherapy, 2013)
The Meaning of Work among Nonstandard Workers: A Multifaceted Reality Abstract A sample of 100 Canadian nonstandard workers completed a semi-structured exploration guide designed to investigate the significance work had for them, its centrality, their expectations for, and personal commitment to this role. This exploratory study revealed that even though work had a positive significance and constituted a central value for most of these participants, its importance in comparison with other life roles was less clear. Moreover, the participants’ precarious situation seemed to color their expectations for and commitment to work. The results are discussed with respect to the scientific literature, and implications for career counseling and research are provided.